1984
DOI: 10.1210/endo-114-4-1364
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Flurbiprofen, a Potent Inhibitor of Prostaglandin Synthesis, on Insulin and Glucagon Release from Isolated Rat Pancreas*

Abstract: The influence of different levels of inhibition of prostaglandin (PG) synthesis on the release of insulin and glucagon was investigated in the basal state (5.6 mM glucose) and in response to 30-min perfusion of 16.7 mM glucose using the isolated perfused rat pancreas model. Flurbiprofen (FLR), a potent and selective inhibitor of PG synthesis, was present in the perfusate during the entire experimental period at a concentration of 10(-8), 5 X 10(-8), or 10(-6) M; control experiments were performed without the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0
2

Year Published

1984
1984
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 51 publications
3
8
0
2
Order By: Relevance
“…In accordance with other authors, we demonstrated that control perfusion of an isolated pancreas does not lead to an elevation of the pancreatic enzymes (amylase, lipase and LDH) in the effluent or a development of pancreatic necrosis within the time of experimentation [4,7,13,14,[16][17][18]. Advantageously, the use of rat as organ source is much more cost-effective than the use of other mammals such as cats or dogs.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In accordance with other authors, we demonstrated that control perfusion of an isolated pancreas does not lead to an elevation of the pancreatic enzymes (amylase, lipase and LDH) in the effluent or a development of pancreatic necrosis within the time of experimentation [4,7,13,14,[16][17][18]. Advantageously, the use of rat as organ source is much more cost-effective than the use of other mammals such as cats or dogs.…”
Section: Discussionsupporting
confidence: 88%
“…In these preparations, the morphological integrity of the exocrine pancreatic cells, especially their functional polarity, cannot be preserved over long incubation time. The isolated perfused rat pancreas which has been used in diabetology for many years may be useful to overcome these limitations [1][2][3][4][5]. Surprisingly, studies into acute pancreatitis in the isolated perfused rat pancreas are very rare [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Palmblad and Higgs reported the potentiation of leukotaxis by indomethacin at lower concentrations in vitro and in vivo [14,15]. The reduction of prostaglandin mediated systemic effects brought about by partial inhibition of cycloxygenase activity can also effect the formation of lipoxygenase metabolites [26,27]. In addition, potentiation of the lipoxygenase pathway may occur as a result of altered substrate availability between the pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In our opinion the isolated perfused rat pancreas presents the following advantages: q The integrity of the pancreas is maintained, for example, the contact to the endocrine pancreatic cells, the connection with the vascular system, and the polarity of the cells to the exocrine pancreatic ducts. q Important physiological regulative mechanisms continue working for a limited time [2,4,5,9,33,34]. The perfusion fluid can be modified very easily, and enzymes, hormones, potentially damaging substances, and therapeutically active substances can be easily added directly to the arterial inflow.…”
Section: Discussionmentioning
confidence: 99%
“…In 1939 Long [1] described a perfusion apparatus for a pulsating perfusion of a rat pancreas. Many authors have improved this model for use in diabetology [2,3,4,5,6,7,8,9,10]. Grodsky et al [3] described the following advantages of an isolated perfused pancreas: q The substances studied can be conveniently maintained at constant and known levels throughout an experiment.…”
Section: Introductionmentioning
confidence: 99%